Amor de salvação à moda de Eça: uma leitura de Alves & Cia - Araújo, Tatiane Santos de (2012)
To investigate a title Alves & Cia by Eça de Queirós that it is at the same time a posthumous publication and not well known by people fostered the present study to pursue understand the role of the adulterer, especially the feminine one, in the fiction and in the ideological projects of Eça de Queirós. As the reader of Eça de Queirós is used to encountering unhappy ends of the adulteress in the author`s narratives, this paper`s purpose is to verify the reasons that led the Portuguese writer to allow, in the intricate, ironic and risible love triangle, the escape of the adulteress from any punishment. Following this intention, this paper is not only concerned to consider the values that constitute the Portuguese mentality nineteenth - feminine condition, women education, the social roles and the adulterer – to better understand the perspectives of the writer but also to evince the differential treatment given by the author to the same themes in his other titles. It is relevant elucidate the counterpoint with the Romantism that Eça de Queirós always tried to insert inside and outside of his titles, as a result of his concern with the negative influence of the romantic idealism in the education of Portuguese society, mainly the education related to women. By recognizing contemporaneity and the plurality of senses that Alves & Cia embodies that the present study itself does not exempt to designate the relevance of the re-fictionalization of the titles that dialogue with other arts like cinema, music and theatre.